Knowledge management framework - Ang, Teng Hong (2008)
Knowledge management (KM) is a management concept that the Government of Singapore is working towards. Ministries are encouraged to utilise KM initiatives to enable the country’s civil services to be more responsive to the changing economic, financial, social and political reality.